Lived Experiences of LGBTQIA+ Community in Administrative Leadership of School Heads - Nieva-Lustanas, Angela (Journal of Interdisciplinary Perspectives, 2025)
This study explored the administrative leadership of LGBTQIA+ school heads in private high schools in the province of Quezon. The interview was the primary tool used in the form of semi-structured interview questions that were systematically crafted to give way to the target respondents based on their lived experience. Coding and thematic analysis were done to deeply analyze the responses from the participants. Based on the findings, the identity politics among school heads were described as having genderless and affirmative leadership. Creating inclusive environments, greater professional leadership, and identity reaffirmation and community acceptance were found useful in surpassing the challenges faced by LGBTQIA+ leaders. Reliving the unconventional leadership representations of LGBTQIA+ school heads focuses on reflecting transformative leadership and advocating inclusivity. In the private school setting, there is many recommendations formulated based on the responses of the participants. Though there are already existing policies on gender responsiveness, there is still room for modification to set clearer, more inclusive, and comprehensive policies. School leaders can make school safe and inclusive for all. Learning institutions can, therefore, foster effective and responsive school culture for LGBTQIA+ educators in their workplace. Undertaking this study discovered the identity politics, struggles, and representations of the LGBTQ+ Community. It explored their significant lived experiences, which became an eye-opener to the current status, experienced struggles, and representation of the LGBTQIA+ school heads, which could leave an impact on the target readers of the substantial contributions of these leaders in administrative leadership and gender studies. The result of the study can bring change among LGBTQIA+ school heads and teachers and encourage administrative change and integration of evidenced-based solutions that support the LBGTQIA+ community.